Progress in silk and silk fiber-inspired polymeric nanomaterials for drug delivery - Pacheco, Marisa O.; Eccles, Lauren E.; Davies, Nickolas A.; Armada, Jostin; Cakley, Alaura S.; Kadambi, Isiri P.; Stoppel, Whitney L. (Frontiers in Chemical Engineering, 2022)
The fields of drug and gene delivery have been revolutionized by the discovery and characterization of polymer-based materials. Polymeric nanomaterials have emerged as a strategy for targeted delivery because of features such as their impressive biocompatibility and improved availability. Use of naturally derived polymers in these nanomaterials is advantageous due to their biodegradability and bioresorption. Natural biopolymer-based particles composed of silk fibroins and other silk fiber-inspired proteins have been the focus of research in drug delivery systems due to their simple synthesis, tunable characteristics, and ability to respond to stimuli. Several silk and silk-inspired polymers contain a high proportion of reactive side groups, allowing for functionalization and addition of targeting moieties. In this review, we discuss the main classes of silk and silk-inspired polymers that are being used in the creation of nanomaterials. We also focus on the fabrication techniques used in generating a tunable design space of silk-based polymeric nanomaterials and detail how that translates into use for drug delivery to several distinct microenvironments.